Peningkatan Hasil Belajar Pendidikan Agama Islam Pada Materi Menyambut Usia Balig Melalui Model Pembelajaran Kooperatif Tipe Take and Give - Elsa, Ai; Evanirosa, Evanirosa; Gradini, Ega; Zuyyina (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN Cipatangga in Islamic Religious Education (PAI) on the topic of Welcoming Puberty through the implementation of the cooperative learning model Take and Give. The problem underlying this research is the low learning outcomes of students on the topic, as reflected in the students' average scores of 67,5, which are still below the expected standard. The research also focuses on creating an active, creative, and engaging learning environment. This Classroom Action Research (CAR) was conducted in two cycles during the first semester of the 2023/2024 academic year, involving 10 students as subjects. Data were collected using observation sheets and tests, analyzed using percentage formulas, and presented descriptively. The results showed a significant improvement in students' average scores from 67.5 in the pre-cycle to 78.5 in the first cycle, and 91.4 in the second cycle. The percentage of students achieving mastery increased from 40% in the pre-cycle to 70% in the first cycle, and 100% in the second cycle. Student activity levels rose from 81% in the first cycle to 90% in the second cycle, while teacher performance increased from 90% to 94%. In conclusion, the Take and Give learning model significantly enhances both the learning process and students' outcomes in Islamic Religious Education. This model is effective and recommended for improving the quality of education at the elementary school level.